Optical coherence tomography reveals distinct patterns of retinal damage in neuromyelitis optica and multiple sclerosis - Schneider, Elisa; Zimmermann, Hanna; Oberwahrenbrock, Timm; Kaufhold, Falko; Kadas, Ella Maria; Petzold, Axel; Bilger, Frieder; Borisow, Nadja; Jarius, Sven; Wildemann, Brigitte; Ruprecht, Klemens; Brandt, Alexander U.; et al. (PLOS ONE, 2013)
Background Neuromyelitis optica (NMO) and relapsing-remitting multiple sclerosis (RRMS) are difficult to differentiate solely on clinical grounds. Optical coherence tomography (OCT) studies investigating retinal changes in both diseases focused primarily on the retinal nerve fiber layer (RNFL) while rare data are available on deeper intra-retinal layers. Objective To detect different patterns of intra-retinal layer alterations in patients with NMO spectrum disorders (NMOSD) and RRMS with focus on the influence of a previous optic neuritis (ON). Methods We applied spectral-domain OCT in eyes of NMOSD patients and compared them to matched RRMS patients and healthy controls (HC). Semi-automatic intra-retinal layer segmentation was used to quantify intra-retinal layer thicknesses. In a subgroup low contrast visual acuity (LCVA) was assessed. Results NMOSD-, MS- and HC-groups, each comprising 17 subjects, were included in analysis. RNFL thickness was more severely reduced in NMOSD compared to MS following ON. In MS-ON eyes, RNFL thinning showed a clear temporal preponderance, whereas in NMOSD-ON eyes RNFL was more evenly reduced, resulting in a significantly lower ratio of the nasal versus temporal RNFL thickness. In comparison to HC, ganglion cell layer thickness was stronger reduced in NMOSD-ON than in MS-ON, accompanied by a more severe impairment of LCVA. The inner nuclear layer and the outer retinal layers were thicker in NMOSD-ON patients compared to NMOSD without ON and HC eyes while these differences were primarily driven by microcystic macular edema. Conclusion Our study supports previous findings that ON in NMOSD leads to more pronounced retinal thinning and visual function impairment than in RRMS. The different retinal damage patterns in NMOSD versus RRMS support the current notion of distinct pathomechanisms of both conditions. However, OCT is still insufficient to help with the clinically relevant differentiation of both conditions in an individual patient.